PKM STRENGTHENING SANTRIS’ QUR’ANIC LITERACY CULTURE THROUGH THE ONE DAY ONE PAGE PROGRAM BASED ON WALI ASUH MENTORSHIP AT NURUL JADID ISLAMIC BOARDING SCHOOL, AL-HASYIMIYAH REGION - Luthviyah Romziana; Aldona Novalika R; Qonita Amilia; Rahmawati; Riska Nur Hidayati; Ulfatul Hasanah (International Journal of Multidisciplinary Reseach, 2026)
The implementation of learning activities and the habituation of Qur’anic reading at Nurul Jadid Islamic Boarding School, particularly in the Al-Hasyimiyah Area, still faces several challenges, including inconsistencies in students’ daily recitation, unstructured mentoring by guardians (wali asuh), and an underdeveloped monitoring system. The One Day One Page Program, which aims to habituate students to read one page of the Qur’an each day, has been implemented; however, it requires further strengthening in terms of mentoring and program management. This Community Service Program (PKM) aims to strengthen the culture of Qur’anic literacy among students through the optimization of the One Day One Page Program based on wali asuh mentoring. The method employed is a descriptive-participatory approach consisting of planning, implementation, monitoring, and evaluation stages. Mentoring was carried out through technical coordination with area administrators and wali asuh, daily submission of one page of Qur’anic recitation to the wali asuh, and weekly monitoring using a simple recording instrument in the Student Activity Book for Female Students (BKSP). Program evaluation was conducted by analyzing daily and weekly recitation records as well as reflective discussions with wali asuh. The results indicate an improvement in students’ consistency in performing daily Qur’anic recitation, enhanced fluency in reading according to proper makhraj and tajwid rules, and a strengthened role of wali asuh in mentoring Qur’anic literacy. Overall, the One Day One Page Program based on wali asuh mentoring has proven to be an effective model for fostering Qur’anic literacy habits that is simple, practical, and sustainable within the pesantren environment.